2019
DOI: 10.1088/1361-648x/ab3890
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property correlation studies of alkaline-earth metal—azides M(N3)2(M  =  Sr, Ba)

Abstract: Inorganic metal azides M(N3)2 (M  =  Sr, Ba) and metal nitrates M(NO3)2 (M  =  Sr, Ba) are interesting materials due to their wide range of industrial usefulness as gas generators, pyrotechnics, photo graphic materials and explosives. In this work, we explore the mechanical, vibrational (infrared, phonon dispersion), Born effective charge (BEC) and thermodynamic properties of these materials to understand the sensitivity correlation studies using plane wave pseudopotential method. As these materials are layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In recent studies, we have found that metal nitrides have attracted more and more attention. 50,51 Because metal nitrides are more stable than pure nitrogen compounds in terms of kinetics, and have the characteristics of low synthesis pressure and superior physical and chemical properties, they can be widely used in the research of high energy-density materials. 3 3.1 CaN 6 with P 1 structure…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, we have found that metal nitrides have attracted more and more attention. 50,51 Because metal nitrides are more stable than pure nitrogen compounds in terms of kinetics, and have the characteristics of low synthesis pressure and superior physical and chemical properties, they can be widely used in the research of high energy-density materials. 3 3.1 CaN 6 with P 1 structure…”
Section: Resultsmentioning
confidence: 99%
“…This section mainly studies the structural properties and stability of SrN 6 , and other forms of strontium nitrogen compounds SrN n (n ¼ 1-6) have been reported. 51 In previous theoretical prediction, many alkali metal nitrides have been studied and proved to be good energy storage materials, such as RbN 3 . 26 Because Sr element is adjacent to Rb element, Rb and its compounds have excellent physical and chemical properties such as easy ionization, radiation resistance, energy storage, etc., and are used in various elds.…”
Section: Srn 6 With P 1 Structurementioning
confidence: 99%